2008
DOI: 10.1002/ange.200803011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biaryl Compounds through Three‐Component Assembly: Ambidentate Effect of the tert‐Butyldimethylsilyl Group for Regioselective Diels–Alder and Hiyama Coupling Reactions

Abstract: Zwei zum Preis von einem: Ein Verfahren zur regiokontrollierten Synthese mehrfach substituierter Biaryle wird vorgestellt. Bei dieser Methode steuert die tert‐Butyldimethylsilyl(TBDMS)‐Gruppe sowohl die regioselektive Diels‐Alder‐Reaktion eines 3‐TBDMS‐Benz‐ins mit einem Furan als auch die anschließende Hiyama‐Kreuzkupplung mit Aryliodiden (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 33 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…Our research group has recently reported that a silyl group attached at the C3 position of benzynes effectively controlled the regiochemistry of their Diels–Alder reaction with substituted furans to give adducts possessing the silyl group and the substituents of the furans in a remote position on the ring 7. Because the silyl groups on aromatic compounds are stable under ordinary conditions and can be replaced with various functional groups including halo, hydroxy, aryl, and alkyl groups,8 the silyl‐group‐control strategy should be widely applicable in providing a solution for the problem of controlling the regioselectivity of various reactions of substituted benzynes.…”
Section: Methodsmentioning
confidence: 99%
“…Our research group has recently reported that a silyl group attached at the C3 position of benzynes effectively controlled the regiochemistry of their Diels–Alder reaction with substituted furans to give adducts possessing the silyl group and the substituents of the furans in a remote position on the ring 7. Because the silyl groups on aromatic compounds are stable under ordinary conditions and can be replaced with various functional groups including halo, hydroxy, aryl, and alkyl groups,8 the silyl‐group‐control strategy should be widely applicable in providing a solution for the problem of controlling the regioselectivity of various reactions of substituted benzynes.…”
Section: Methodsmentioning
confidence: 99%
“…[7b] The larger alkyl groups of 2 increased both the selectivity and the yield (Table 1, entries 2 and 3). The steric effect of the substituents, though, was less than that of the corresponding silylbenzynes in similar Diels-Alder reactions [9]. The reactions of 2-trimethylsilylfuran (2 d) (Table 1, entry 4) and 2-tributylstannylfuran (2 e) (entry 5) exclusively gave the anti adducts (4 e and 4 f).…”
mentioning
confidence: 86%
“…The following two points are also worth noting from the viewpoint of benzyne chemistry: Firstly, the boryl groups (Bpin = pinacolboryl) were found to favor the highly regioselective Diels-Alder reactions of unsymmetrically substituted benzynes with furans 2 or pyrroles 3, in contrast to most of the previously reported cases. [6][7][8] Secondly, the regioselectivities of the Diels-Alder reaction of 1 resembled those of the 3-silylbenzynes, [9] but the boryl groups exerted different effects than the silyl groups.…”
mentioning
confidence: 99%
“…1-Naphthol scaffolds are commonly occurring features in pharmaceuticals and natural products. [7,8] Our method allows the facile assembly of multisubstituted 1-naphthols under mild reaction conditions.…”
mentioning
confidence: 99%